Healthy Hands: Development and Evaluation of a Knowledge Transfer Program - Nurul Azmawati Mohamed @ Abd Aziz; Zarini Ismail; Jamaluddin T.Z.M.T.; Rani M.D.M.; Ramli S.; Faroque H.; Samad F.N.A.; Ariffien A.R.; Farid A.A.R.C.A.; Isahak I. (UPM Press, 2024)
Indexed by SCOPUS